Environmental Issues in Political Discourse in Britain and Ireland. - Leydier, Gilles (Cambridge Scholars Publishing, 2013)
This book examines the political response to current environmental concerns in the context of the British Isles. How have the issues been assimilated by political parties? Which ones have been given priority? Who are the main actors and what is the role of ecologists? Answers to questions such as these are provided in this collective work, not only through valuable insights into the theories and concepts found in political ecology, but also with specific examination of present political deba ...